Effect of Credit Restructuring During the Covid-19 Pandemic on Financial Performance with Expected Credit Loss as an Intervening Variable - Lauria Arisandy Zalukhu; Fifi Swandari (Universitas Negeri Makassar, 2023)
Credit restructuring is an improvement effort made by the Bank in lending activities to debtors who are experiencing difficulties in fulfilling their obligations. This study aims to analyze the effect of implementing credit restructuring through Expected Credit Loss (ECL) on financial performance during the Covid-19 pandemic. This research is a type of causality research with a quantitative approach that uses secondary data obtained from the financial reports of 21 (twenty one) branch offices of PT Bank Negara Indonesia (Persero), Tbk during the period March 2020 to December 2021. The sampling technique uses a non-probability sampling technique with a saturated sampling technique and the data analysis tool in this study uses the SmartPLS application with an evaluation model that can be carried out by assessing the outer model and the inner model. The results of the analysis show that (1) credit restructuring during the Covid-19 pandemic had a positive effect on financial performance, (2) credit restructuring during the Covid-19 pandemic through expected credit loss as an intervening variable had a positive effect on financial performance. According to researchers, this is because the credit facility provided by the Covid restructuring scheme does not require additional reserves for impairment losses expected credit loss.